The endangered Brown Shrike subspecies Lanius cristatus superciliosus has a male-biased sex ratio and only early arriving males are paired. Issue 1 (8th March 2022) - MIZUMURA, HARUKA; KUBOTA, KOHEI; HIGUCHI, HIROYOSHI
Summary: Along with many long-distance migrant passerine species in the East Asian-Australasian Flyway, the migratory Brown Shrike Lanius cristatus superciliosus has been sharply declining throughout its breeding range. Its breeding range in Japan shrank by 90.9% between the 1910s and 2010s. In contrast, the closely related but resident Bull-headed Shrike L. bucephalus bucephalus has been gradually declining but is still a common resident in Japan. To better understand the drastic decline of Brown Shrike, we compared the pairing success during three consecutive breeding seasons of these two species. About 60–70% of Brown Shrike males were unpaired, which was much higher than the percentage of unpaired male Bull-headed Shrike (c.0–20%). Brown Shrike males arriving later did not pair because the population's sex proportion is heavily biased toward males. One of the factors of male-biased population of Brown Shrike may be female-biased mortality in wintering sites, or on the migratory journey, and tracking studies will be required to test this.